Time-resolved fluorescence in lipid bilayers: selected applications and advantages over steady state - Amaro, Mariana; Šachl, Radek; Jurkiewicz, Piotr; Coutinho, Ana; Prieto, Manuel; Hof, Martin (Biophysical journal, 2014)
Fluorescence methods are versatile tools for obtaining dynamic and topological information about biomembranes because the molecular interactions taking place in lipid membranes frequently occur on the same timescale as fluorescence emission. The fluorescence intensity decay, in particular, is a powerful reporter of the molecular environment of a fluorophore. The fluorescence lifetime can be sensitive to the local polarity, hydration, viscosity, and/or presence of fluorescence quenchers/energy acceptors within several nanometers of the vicinity of a fluorophore. Illustrative examples of how time-resolved fluorescence measurements can provide more valuable and detailed information about a system than the time-integrated (steady-state) approach will be presented in this review: 1), determination of membrane polarity and mobility using time-dependent spectral shifts; 2), identification of submicroscopic domains by fluorescence lifetime imaging microscopy; 3), elucidation of membrane leakage mechanisms from dye self-quenching assays; and 4), evaluation of nanodomain sizes by time-resolved Förster resonance energy transfer measurements.
Keywords: Fluorescence Resonance Energy Transfer; Lipid Bilayers; Fluorescent Dyes; Kinetics; Microscopy, Fluorescence; lipidové dvojvrstvy; rezonanční přenos fluorescenční energie; kinetika; fluorescenční barviva; fluorescenční mikroskopie